Challenges and emerging strategies for next generation liposomal based drug delivery: an account of the breast cancer conundrum - Moudgil, Aliesha; Salve, Rajesh; Gajbhiye, Virendra; Chaudhari, Bhushan P. (Chemistry and Physics of Lipids, 2023)
The global cancer burden is witnessing an upsurge with breast cancer surpassing other cancers worldwide. Furthermore, an escalation in the breast cancer caseload is also expected in the coming years. The conventional therapeutic regimens practiced routinely are associated with many drawbacks to which nanotechnological in-terventions offer a great advantage. But how eminent could liposomes and their advantages be in superseding these existing therapeutic modalities? A solution is reflected in this review that draws attention to a decade-long journey embarked upon by researchers in this wake. This text is a comprehensive discussion of liposomes, the front runners of the drug delivery systems, and their active and passive targeting approaches for breast cancer management. Active targeting has been studied over the decade by many receptors overexpressed on the breast cancer cells and passive targeting with many drug combinations. The results converge on the fact that the actively targeted formulations exhibit a superior efficacy over their non-targeted counterparts and the all lipo-somal formulations are efficacious over the free drugs. This undoubtedly underlines the dominion of liposomal formulations over conventional chemotherapy. These investigations have led to the development of different liposomal formulations with active and passive targeting capacities that could be explored in depth. Acknowl-edging and getting a deeper insight into the liposomal evolution through time also unveiled many imperfections and unchartered territories that can be explored to deliver dexterous liposomal formulations against breast cancer and more in the clinical trial pipeline.
Keywords: Breast cancer; Liposomal metamorphosis; Receptor-ligand dynamics; Targeted Drug Delivery